PROJECT-BASED LEARNING INTEGRATING ISLAMIC SOCIAL VALUES: IMPLICATIONS FOR SOCIAL ATTITUDE DEVELOPMENT IN PRIMARY EDUCATION: PEMBELAJARAN BERBASIS PROYEK YANG MENGINTEGRASIKAN NILAI-NILAI SOSIAL ISLAM: IMPLIKASI TERHADAP PENGEMBANGAN SIKAP SOSIAL DALAM PENDIDIKAN DASAR - Keysa Aura Fadila; Muhlasin Amrullah; Vanda Rezania (SOSIOEDUKASI, 2026)
This study aims to analyze the effect of implementing a Project Based Learning (PBL) model integrated with the social values of Surah Al-Ma’un on elementary school students’ social attitudes. The research employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The participants were 30 fifth-grade students of SDN Wonoplintahan 2, Sidoarjo Regency, selected through purposive sampling. The research instrument was a validated social attitude test. Data were analyzed using the Shapiro–Wilk normality test, paired sample t-test, and effect size calculation (eta squared). The results indicated a statistically significant improvement in students’ social attitudes after the implementation of PBL integrated with the values of QS. Al-Ma’un, with a significance value of 0.000 (p < 0.05). The effect size was categorized as very large. These findings demonstrate that integrating PBL with religious values effectively enhances students’ empathy, social care, cooperation, and social responsibility, and supports character education in elementary schools.